Development of chitosan-graphene oxide active layers for detection of cobalt ion using surface plasmon resonance optical sensor - Saleviter, Silvan (2019)
The development of chitosan-graphene oxide based active layer namely chitosan- graphene oxide-cadmium sulphide quantum dots (chitosan-GO-CdS QDs) thin film and chitosan-graphene oxide-4−(2−pyridylazo)resorcinol (chitosan-GO-PAR) thin film for the detection of cobalt ion (Co²⁺) by using surface plasmon resonance optical sensor has been studied. The synthesized thin films were confirmed by Fourier transform infrared spectrum by showing the functional groups of the composites. The optical properties of the composite thin films were characterized by using UV-Vis-NIR absorption spectroscopy where the absorbance peaks of the thin films can be observed in the range of 220 nm to 300 nm, and the band gaps are 4.033 eV and 4.066 eV for chitosan-GO- CdS QDs and chitosan-GO-PAR thin film respectively. From the Atomic Force Microscope (AFM) images, the addition of graphene oxide increased the roughness of the composite thin films and the presence of cadmium sulphide quantum dot was observed using Transmission Electron Microscope (TEM). Then, the prepared thin films were successfully used as the active layer for the detection of Co²⁺ in solution. The sensor showed good results and produced some linear responses as the concentration of the Co²⁺ were increased. At lower concentration, the chitosan-GO-PAR active layer showed higher sensitivity that is 0.2370° ppm⁻¹, compared to the chitosan-GO-CdS QDs active layer with sensitivity of 0.1188° ppm⁻¹. In addition, the calibration curve of the angle shift data using Sips model shows that the active layers can attract the cobalt which is proven by the high binding affinity of 1.649 ppm⁻¹ for the gold (Au) modified with chitosan-GO-PAR active layer and 0.939 ppm⁻¹ for the gold modified with chitosan-GO- CdS QDs active layer.